A cationic barium titanate-cellulose nanocomposite film and preparation method thereof

By coating barium titanate nanoparticles with polydopamine and cationized, and combining nanocellulose, a cationized barium titanate-cellulose nanocomposite film was prepared, which solved the dielectric loss and breakdown strength problems caused by the agglomeration of filler particles, and achieved efficient dielectric and mechanical properties.

CN116239825BActive Publication Date: 2025-04-04SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310304489.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-04-04
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

When existing inorganic high-dielectric fillers are directly doped into nanocellulose, filler particles are prone to agglomeration, resulting in increased dielectric loss and sharp reduction in breakdown strength.

Method used

The cationized barium titanate nanoparticles are coated with polydopamine, the active group -NH2 is introduced, and the quaternary ammonium is introduced through a cationic etherifying agent. It was then blended with nanocellulose, and a cationized barium titanate-cellulose nanocomposite film was prepared by sonication and vacuum-assisted suction filtration.

Benefits of technology

The dispersion of barium titanate nanoparticles and binding force with nanocellulose are improved, dielectric loss is reduced, breakdown strength is enhanced, and good dispersion and mechanical strength are maintained under high load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239825B_ABST
    Figure CN116239825B_ABST
Patent Text Reader

Abstract

The invention discloses a cationized barium titanate-cellulose nanocomposite film and a preparation method thereof. The method comprises: preparing barium titanate wrapped by polydopamine by using barium titanate nanoparticles; immersing the barium titanate wrapped by polydopamine in a cationic etherifying agent solution, stirring for reaction, washing, and drying to obtain cationized barium titanate; wherein the cationic etherifying agent in the cationic etherifying agent solution contains a quaternary ammonium group; blending the cationized barium titanate with nanocellulose, and ultrasonically treating to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension; vacuum-assisted filtration is performed on the uniformly dispersed cationized barium titanate / nanocellulose suspension to obtain a cationized barium titanate-cellulose nanocomposite film; the invention avoids agglomeration of filler particles in a matrix, avoids the generation of leakage paths, effectively reduces dielectric loss, and enhances breakdown strength, and has green degradability and good dielectric and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of green high-dielectric composite materials, and particularly relates to a cationized barium titanate-cellulose nanocomposite film and a preparation method thereof. Background Art

[0002] Dielectric materials refer to materials that can undergo polarization, conductivity, loss and breakdown under the action of an external electric field. Materials with a dielectric constant greater than that of silicon dioxide (ε=3.9) are generally referred to as high dielectric materials. High dielectric materials have excellent electric field uniformity, high energy storage and fast charge and discharge rates. They are widely used in electronic and electrical fields such as capacitor components, storage devices, high-voltage transmission lines, electric pulse equipment and modern communication equipment.

[0003] Traditional high dielectric materials are mainly inorganic ceramics. Although they have extremely strong polarization ability and ultra-high dielectric constant, the high porosity of ceramic materials prepared by high-temperature sintering makes the dielectric loss of ceramic dielectric materials large and the breakdown strength low. In addition, the ceramics themselves are brittle and not conducive to processing and molding, so their application prospects are limited. At the same time, compared with ceramic materials, single synthetic polymers have excellent processability, mechanical properties, flexibility, low dielectric loss and high breakdown strength, but their dielectric constant is relatively low and difficult to be biodegraded. The large amount of waste generated after use seriously harms the environment.

[0004] As a biodegradable natural polymer material, cellulose nanofibers have excellent characteristics such as high aspect ratio, high strength and high modulus, and good light transmittance. In addition, cellulose nanofiber molecules contain polar groups such as -COOH and -OH. In an external electric field, the directional deflection of a large number of dipoles will produce a strong polarization effect, making it have a dielectric constant comparable to that of the synthetic polymer PVDF. However, compared with inorganic ceramic fillers, cellulose materials have a lower dielectric constant, and their porous structure and hydrophilicity lead to low breakdown strength and unstable charge storage, which seriously limits their application in the field of high energy storage electronic devices.

[0005] At present, inorganic high dielectric fillers are also directly doped into nanocellulose to improve the dielectric constant of the composite material. However, as the amount of functional fillers added increases, the filler particles are very likely to agglomerate in the matrix, forming structural defects such as micropores and holes, and generating leakage paths, thereby increasing dielectric loss and sharply reducing breakdown strength. At the same time, the mechanical properties and flexibility of the material will also decrease. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the present invention provides a cationic barium titanate-cellulose nanocomposite film and a preparation method thereof, so as to solve the technical problem that when the existing inorganic high dielectric filler is directly doped into nanocellulose to improve the dielectric constant of the composite material, the filler particles are very likely to agglomerate in the matrix, resulting in increased dielectric loss and a sharp decrease in breakdown strength.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The present invention provides a method for preparing a cationized barium titanate-cellulose nanocomposite film, comprising the following steps:

[0009] Step 1, using barium titanate nanoparticles to prepare barium titanate wrapped by polydopamine;

[0010] Step 2, immersing the barium titanate wrapped by polydopamine in a cationic etherifying agent solution, stirring for reaction, washing, and drying to obtain a cationized barium titanate; wherein the cationic etherifying agent in the cationic etherifying agent solution contains a quaternary ammonium group;

[0011] Step 3, blending the cationized barium titanate and nanocellulose, and ultrasonically treating to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension;

[0012] Step 4: performing vacuum-assisted filtration on the uniformly dispersed cationic barium titanate / nanocellulose suspension to obtain the cationic barium titanate-cellulose nanocomposite film.

[0013] Furthermore, in step 1, the process of preparing barium titanate encapsulated by polydopamine using barium titanate nanoparticles is as follows:

[0014] The barium titanate nanoparticles are placed in a Tris solution, the pH value is adjusted, dopamine hydrochloride is added, the mixture is stirred for reaction, and then washed and dried to obtain the barium titanate wrapped by polydopamine.

[0015] Furthermore, the mass ratio of the dopamine hydrochloride to the barium titanate nanoparticles is (0.5-2):10.

[0016] Furthermore, in step 2, the barium titanate wrapped by polydopamine is immersed in a cationic etherifying agent solution, stirred for reaction, washed, and dried to obtain a cationic barium titanate, which is specifically as follows;

[0017] The barium titanate wrapped by polydopamine is immersed in an excess of a cationic etherifying agent solution, stirred at 60-90° C. with a magnetic rotor for 6-12 hours, washed, and dried to obtain a cationic barium titanate; wherein the concentration of the cationic etherifying agent solution is 25-40wt.%.

[0018] Furthermore, in step 2, the cationic etherifying agent is 2,3-epoxypropyltrimethylammonium chloride.

[0019] Furthermore, in step 2, the drying conditions are: temperature of 60-105° C., vacuum drying for 4-12 hours.

[0020] Furthermore, in step 3, the cationized barium titanate and nanocellulose are mixed in a mass ratio of (1-5):(5-9); the mass concentration of the uniformly dispersed cationized barium titanate / nanocellulose suspension is 0.05%-0.1%.

[0021] Furthermore, in step 3, the nanocellulose is carboxyl-rich nanocellulose oxidized by TEMPO.

[0022] The invention also provides a cationized barium titanate-cellulose nanocomposite film, which is prepared by using the preparation method of the cationized barium titanate-cellulose nanocomposite film.

[0023] Furthermore, the cationic barium titanate-cellulose nanocomposite film is 3 The dielectric constant at Hz is 13.6-116.2, and the mechanical strength is 58-83Mpa.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The invention provides a cationized barium titanate-cellulose nanocomposite film and a preparation method thereof. The invention comprises the following steps: firstly, barium titanate is coated with polydopamine to introduce an active group -NH2, and then a cationic etherifying agent containing a quaternary ammonium group reacts with the active group -NH2 to generate a ring-opening reaction, thereby introducing a quaternary ammonium root, and finally obtaining cationized barium titanate. When the cationized barium titanate is used as a filler and mixed with nanocellulose as a matrix, electrostatic repulsion is introduced into the cationized barium titanate on the basis of the adhesion of the polydopamine itself, thereby not only improving the dispersibility of barium titanate nanoparticles themselves, but also improving the binding force with the negatively charged matrix nanocellulose, increasing the retention rate of nanoparticles, reducing the two-sidedness of the material, improving the dispersibility of the material, avoiding the agglomeration of filler particles in the matrix, thereby avoiding the generation of leakage paths, effectively reducing dielectric loss, and enhancing breakdown strength. When the content of the barium titanate nanoparticle filler is 40wt.%, the composite film still has excellent dispersibility, and while the dielectric properties are enhanced, the mechanical strength is not greatly affected. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a flow chart of the preparation method of the cationic barium titanate-cellulose nanocomposite film of the present invention;

[0027] Figure 2 The dielectric constant curve of the cationic barium titanate-cellulose nanocomposite film prepared in Examples 1-3;

[0028] Figure 3 This is the SEM image of the cationic barium titanate-cellulose nanocomposite film prepared in Example 2. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail in the following specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] As attached Figure 1 As shown, the present invention provides a method for preparing a cationized barium titanate-cellulose nanocomposite film, comprising the following steps:

[0031] Step 1: using barium titanate nanoparticles to prepare barium titanate wrapped by polydopamine; wherein the preparation process of the barium titanate wrapped by polydopamine is as follows:

[0032] The barium titanate nanoparticles are placed in a Tris solution and the pH is adjusted to 8.0-8.5; then dopamine hydrochloride is added, stirred for reaction, washed, and dried to obtain the barium titanate wrapped by polydopamine; wherein the mass ratio of dopamine hydrochloride to the barium titanate nanoparticles is (0.5-2):10.

[0033] Step 2, immersing the barium titanate wrapped by polydopamine in a cationic etherifying agent solution, stirring for reaction, washing, and drying to obtain a cationized barium titanate; wherein the cationic etherifying agent in the cationic etherifying agent solution contains a quaternary ammonium group; wherein the specific process is as follows:

[0034] The barium titanate wrapped by polydopamine is immersed in an excess of a cationic etherifying agent solution, and reacted for 6-12 hours at 60-90° C. with a magnetic rotor for stirring; wherein the concentration of the cationic etherifying agent solution is 25-40wt.%; the cationic etherifying agent is 2,3-epoxypropyltrimethylammonium chloride; and the drying conditions are: temperature of 60-105° C. and vacuum drying for 4-12 hours.

[0035] Step 3, blending the cationized barium titanate and nanocellulose, and ultrasonically treating them to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension; wherein the cationized barium titanate and nanocellulose are mixed in a mass ratio of (1-5): (5-9); the mass concentration of the uniformly dispersed cationized barium titanate / nanocellulose suspension is 0.05%-0.1%; and the nanocellulose is carboxyl-rich nanocellulose oxidized by TEMPO.

[0036] Step 4: performing vacuum-assisted filtration on the uniformly dispersed cationic barium titanate / nanocellulose suspension to obtain the cationic barium titanate-cellulose nanocomposite film.

[0037] The cationic barium titanate-cellulose nanocomposite film of the present invention is green and degradable and has good dielectric and mechanical properties; wherein the dielectric properties of the composite film material are 10 3 The Hz reaches 13.6-116.2, and the mechanical strength is 58-83Mpa.

[0038] Preparation principle:

[0039] The cationic barium titanate-cellulose nanocomposite film and the preparation method thereof of the present invention comprises the following steps: modifying the surface of barium titanate nanoparticles by coating with polydopamine having super strong adhesion, thereby introducing active groups; wherein the active groups are amino groups; and then allowing the amino groups to undergo a ring-opening reaction with a cationic etherifying agent, thereby introducing quaternary ammonium groups, and finally obtaining a positively charged nanofiller; and then compounding the positively charged nanofiller with negatively charged TEMPO oxidized nanocellulose, thereby introducing electrostatic repulsion on the basis of the adhesion of the polydopamine itself, which not only improves the dispersibility of the nanoparticles themselves, but also generates more interface polarization, thereby increasing the dielectric constant; and at the same time, improves the binding force with the matrix TOCNF, which is reflected in the increase in the retention rate of the nanoparticles and the reduction in the two-sidedness of the material, so that the composite film can still maintain good dispersibility under a high loading amount of the nanoparticles, and its dielectric properties are enhanced while the mechanical strength is not greatly affected.

[0040] Example 1

[0041] This embodiment 1 provides a method for preparing a cationic barium titanate-cellulose nanocomposite film, which specifically includes the following steps:

[0042] Step 1. Dry barium titanate nanoparticles (BTO) under vacuum at 60°C for 12 hours to remove moisture to obtain dry barium titanate nanoparticles; then, accurately weigh 1 g of the dry barium titanate nanoparticles and place them in 200 mL of 1.2 g / L Tris solution, then adjust the pH to 8.0 with 0.1 M HCl, add 0.05 g of dopamine hydrochloride (DA-HCl), and stir with a magnetic rotor at room temperature for 24 hours; after the reaction is completed, wash the product with deionized water, and then vacuum dry it at 60°C for 4 hours to obtain barium titanate wrapped by polydopamine, which is recorded as BTO@PDA.

[0043] Step 2: Immerse the barium titanate wrapped by polydopamine in an excess of 25wt.% 2,3-epoxypropyltrimethylammonium chloride solution, stir the reaction with a magnetic rotor at 70°C for 12 hours, and then remove the solvent that does not participate in the reaction with deionized water and anhydrous ethanol respectively; then, vacuum dry at 60°C for 12 hours to obtain cationic barium titanate.

[0044] Step 3: 5 mg of cationized barium titanate, 45 mg of nanocellulose with an absolute dry mass and water are mixed, and ultrasonic treatment is performed for 30 minutes to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension; wherein the nanocellulose is carboxyl-rich nanocellulose oxidized by TEMPO; and the mass concentration of the uniformly dispersed cationized barium titanate / nanocellulose suspension is 0.1%.

[0045] Step 4: vacuum-assisted filtration is performed on the uniformly dispersed cationic barium titanate / nanocellulose suspension to obtain the cationic barium titanate-cellulose nanocomposite film.

[0046] Performance testing:

[0047] The performance of the cationic barium titanate-cellulose nanocomposite film prepared in Example 1 was tested. The test results showed that the mechanical strength of the cationic barium titanate-cellulose nanocomposite film was 83 MPa, and the dielectric constant was 10 3 Hz reaches 13.6.

[0048] Example 2

[0049] This embodiment 2 provides a method for preparing a cationic barium titanate-cellulose nanocomposite film, which specifically includes the following steps:

[0050] Step 1. Dry barium titanate nanoparticles (BTO) at 105°C in vacuum for 4 hours to remove moisture to obtain dry barium titanate nanoparticles; then, accurately weigh 1 g of the dry barium titanate nanoparticles and place them in 200 mL of 1.2 g / L Tris solution, then adjust the pH to 8.5 with 0.1 M HCl, add 0.2 g of dopamine hydrochloride (DA-HCl), and stir with a magnetic rotor at room temperature for 24 hours; after the reaction is completed, wash the product with deionized water, and then vacuum dry it at 105°C for 4 hours to obtain barium titanate wrapped by polydopamine, which is recorded as BTO@PDA.

[0051] Step 2: Immerse the barium titanate wrapped by polydopamine in an excess of 40wt.% 2,3-epoxypropyltrimethylammonium chloride solution, stir with a magnetic rotor at 90°C for 6 hours, and then remove the solvent that does not participate in the reaction with deionized water and anhydrous ethanol respectively; then, vacuum dry at 105°C for 4 hours to obtain cationic barium titanate.

[0052] Step 3: 20 mg of cationized barium titanate, 30 mg of nanocellulose with an absolute dry mass and water are mixed, and ultrasonic treatment is performed for 30 minutes to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension; wherein the nanocellulose is carboxyl-rich nanocellulose oxidized by TEMPO; and the mass concentration of the uniformly dispersed cationized barium titanate / nanocellulose suspension is 0.05%.

[0053] Step 4: vacuum-assisted filtration is performed on the uniformly dispersed cationic barium titanate / nanocellulose suspension to obtain the cationic barium titanate-cellulose nanocomposite film.

[0054] Performance testing:

[0055] The performance of the cationic barium titanate-cellulose nanocomposite film prepared in Example 2 was tested. The test results showed that the mechanical strength of the cationic barium titanate-cellulose nanocomposite film was 70.5 MPa, and the dielectric constant was 10 3 It reaches 116.2 at Hz.

[0056] Example 3

[0057] This embodiment 3 provides a method for preparing a cationic barium titanate-cellulose nanocomposite film, which specifically includes the following steps:

[0058] Step 1. Dry barium titanate nanoparticles (BTO) at 80°C in vacuum for 7h to remove moisture to obtain dry barium titanate nanoparticles; then, accurately weigh 1g of the dry barium titanate nanoparticles and place them in 200mL of 1.2g / L Tris solution, then adjust the pH to 8.5 with 0.1M HCl, add 0.05g of dopamine hydrochloride (DA-HCl), and stir with a magnetic rotor at room temperature for 24h; after the reaction is completed, wash the product with deionized water, and then vacuum dry it at 80°C for 7h to obtain barium titanate wrapped by polydopamine, which is recorded as BTO@PDA.

[0059] Step 2: Immerse the barium titanate wrapped by polydopamine in an excess of 30wt.% 2,3-epoxypropyltrimethylammonium chloride solution, stir with a magnetic rotor at 60°C for 9h, and then remove the solvent that does not participate in the reaction with deionized water and anhydrous ethanol respectively; then, vacuum dry at 80°C for 7h to obtain cationic barium titanate.

[0060] Step 3: Mix 25 mg of cationized barium titanate, 25 mg of nanocellulose with an absolute dry mass, and water, and perform ultrasonic treatment for 30 minutes to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension; wherein the nanocellulose is carboxyl-rich nanocellulose oxidized by TEMPO; and the mass concentration of the uniformly dispersed cationized barium titanate / nanocellulose suspension is 0.05%.

[0061] Step 4: vacuum-assisted filtration is performed on the uniformly dispersed cationic barium titanate / nanocellulose suspension to obtain the cationic barium titanate-cellulose nanocomposite film.

[0062] Performance testing:

[0063] The performance of the cationic barium titanate-cellulose nanocomposite film prepared in Example 3 was tested. The test results showed that the mechanical strength of the cationic barium titanate-cellulose nanocomposite film was 58 MPa, and the dielectric constant was 10 3 Hz up to 24.

[0064] As attached Figure 2 As shown, attached Figure 2 The dielectric constant diagrams of the cationic barium titanate-cellulose nanocomposite films prepared in Examples 1-3 at different frequencies are given in the attached Figure 2 It can be seen that the dielectric constant of the material can be fully improved only when the amount of modified particles added is large and the surface cationization modification is sufficient.

[0065] As attached Figure 3 As shown, attached Figure 3The SEM image of the cationic barium titanate-cellulose nanocomposite film prepared in Example 2 is given in the attached Figure 2 It can be seen that the cationic barium titanate has good dispersion in the nanocellulose matrix and no obvious agglomeration phenomenon occurs.

[0066] The cationized barium titanate-cellulose nanocomposite film and the preparation method thereof of the present invention introduce active groups, namely, amino groups, on the surface of barium titanate nanoparticles through surface coating modification with polydopamine, and then the amino groups are further subjected to a ring-opening reaction with a cationic etherifying agent (2,3-epoxymethylpropyltrimethylammonium chloride, GTMAC) to introduce quaternary ammonium groups, and finally a positively charged nanofiller is obtained, which is then blended with TEMPO-oxidized nanocellulose, diluted with water, and ultrasonically dispersed, and a cationized barium titanate / nanocellulose composite film is prepared by a vacuum-assisted molding method. The present invention introduces electrostatic repulsion on the basis of the adhesion of polydopamine itself, which not only improves the dispersibility of the nanoparticles themselves, but also improves the binding force with the negatively charged matrix TOCNF, increases the retention rate of the nanoparticles, and reduces the two-sidedness of the material. The composite film still has excellent dispersibility under a high loading amount of nanoparticles, and its dielectric properties are enhanced while the mechanical strength is not greatly affected, providing a new idea for the preparation of environmentally friendly cellulose-based high dielectric composite materials.

[0067] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.

Claims

1. A method for preparing a cationic barium titanate-cellulose nanocomposite film, characterized in that: The following steps are involved: Step 1, using barium titanate nanoparticles to prepare barium titanate wrapped by polydopamine; Step 2, immersing the barium titanate wrapped by polydopamine in a cationic etherifying agent solution, stirring for reaction, washing, and drying to obtain a cationized barium titanate; wherein the cationic etherifying agent in the cationic etherifying agent solution contains a quaternary ammonium group; Step 3, blending the cationized barium titanate and nanocellulose, and ultrasonically treating to obtain a uniformly dispersed cationized barium titanate / nanocellulose suspension; the nanocellulose is TEMPO-oxidized carboxyl-rich nanocellulose; Step 4: performing vacuum-assisted filtration on the uniformly dispersed cationic barium titanate / nanocellulose suspension to obtain the cationic barium titanate-cellulose nanocomposite film.

2. The method for preparing a cationic barium titanate-cellulose nanocomposite film according to claim 1, characterized in that: In step 1, the process of preparing barium titanate encapsulated by polydopamine using barium titanate nanoparticles is as follows: The barium titanate nanoparticles are placed in a Tris solution, the pH value is adjusted, dopamine hydrochloride is added, the mixture is stirred for reaction, and then washed and dried to obtain the barium titanate wrapped by polydopamine.

3. The method for preparing a cationic barium titanate-cellulose nanocomposite film according to claim 2, characterized in that: The mass ratio of the dopamine hydrochloride to the barium titanate nanoparticles is (0.5-2):

10.

4. The method for preparing a cationized barium titanate-cellulose nanocomposite film according to claim 1, characterized in that: In step 2, the barium titanate wrapped by polydopamine is immersed in a cationic etherifying agent solution, stirred for reaction, washed, and dried to obtain a cationic barium titanate, which is specifically as follows; The barium titanate wrapped by polydopamine is immersed in an excess of a cationic etherifying agent solution, stirred at 60-90° C. with a magnetic rotor for 6-12 hours, washed, and dried to obtain a cationic barium titanate; wherein the concentration of the cationic etherifying agent solution is 25-40wt.%.

5. The method for preparing a cationic barium titanate-cellulose nanocomposite film according to claim 1, characterized in that: In step 2, the cationic etherifying agent is 2,3-epoxypropyltrimethylammonium chloride.

6. The method for preparing a cationic barium titanate-cellulose nanocomposite film according to claim 1, characterized in that: In step 2, the drying conditions are: temperature of 60-105° C., vacuum drying for 4-12 hours.

7. The method for preparing a cationic barium titanate-cellulose nanocomposite film according to claim 1, characterized in that: In step 3, the cationized barium titanate and nanocellulose are mixed in a mass ratio of (1-5):(5-9); the mass concentration of the uniformly dispersed cationized barium titanate / nanocellulose suspension is 0.05%-0.1%.

8. A cationic barium titanate-cellulose nanocomposite film, characterized in that: The film is prepared by the method for preparing a cationized barium titanate-cellulose nanocomposite film as described in any one of claims 1 to 7.

9. The cationized barium titanate-cellulose nanocomposite film according to claim 8, characterized in that: The cationic barium titanate-cellulose nanocomposite film is 3 The dielectric constant at Hz is 13.6-116.2, and the mechanical strength is 58-83Mpa.